(untitled) (International Seven Journal of Multidisciplinary, 2024)
Background: Dyslipidemia is caused by an increase in plasma lipoprotein levels and predisposes to the risk of thrombotic events, which highlights the need for early treatment. Traditional therapies have limitations due to the lack of adequate responses and abandonment of treatment due to its adverse effects. Aim: This study sought to identify alternative treatments for dyslipidemia using herbal medicines, which could help traditional methods or replace them. Methods: A systematic review was carried out by searching the Latin American and Caribbean Literature in Health Sciences (Lilacs), PubMed and ScienceDirect databases using the descriptors "phytotherapy" OR "phytotherapeutic drugs" AND "dyslipidemias" OR "cholesterol" OR "atherosclerosis". Results: The databases returned 80 articles, 9 were excluded for being duplicates and after applying the exclusion and inclusion criteria resulted in a sample of 13 articles. Studies with herbal medicines such as Red Grape Seed Extract (RGSE), Sacha Inchi Oil, Green Tea, Eggplant Juice, Agrimonia eupatoria, Artichoke and Garlic, which showed different effects on lipid profiles, were evaluated. Conclusion: The use of herbal medicines in the treatment of dyslipidemia may be a viable alternative, but further studies are needed on this subject.